An Innovative Approach to Improve the System of Quality Management System at the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The аrticle reveals the essence of such concepts as process, business process, reengineering, system of quality management. The paper presents the characteristics of improving the quality management system at the enterprise business process re-engineering and its usage to improve the efficiency of enterprise management.Is established that an effective way of sustainable development of the enterprise is improving the Organization of production on the basis of the existing quality management system. experience of foreign and domestic practice of certification of quality management systems іs the generalized. As part of the quality management system were proposed measures that will ensure the production of quality products. Suggested the creation of an optimal quality management system management based on the results of modeling business.Сertification of quality management systems in accordance with the requirements of standard ISO 9001 іs a significant factor in the competitive struggle for the conquest of markets.
Keywords: quality, quality management system, process, business process, system of quality management, competitiveness, reengineering